Analisis Pencapaian SDGs 7 Affordable and Clean Energy di Bidang Ketenaga Listrikan pada Pemprov Jawa Barat - Rafarza Muhammadi; Razika Bilqis; Najla Fathina Aulia; Iyep Saefulrahman (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study examines the extent to which West Java Province has achieved Sustainable Development Goal (SDG) 7 on clean and affordable energy in the electricity sector. The study uses a qualitative method with a case study approach to evaluate policies and achievements in terms of energy access, renewable energy use, energy efficiency, and the dynamics of cooperation between government agencies. The results show that the electrification rate in West Java has almost reached 100% thanks to government policies such as the free electricity program for underprivileged communities. However, the share of renewable energy in the province was still around 15% in 2022, which has not yet reached the target of 17% by 2025. Furthermore, energy efficiency is also an important issue because primary energy consumption in West Java increased in 2022. This study emphasizes the need to enhance inter-agency cooperation, innovation in local policies, and political commitment to achieve SDG 7 targets in line with national directives.